A Versatile Ionomer‐Based Soft Actuator with Multi‐Stimulus Responses, Self‐Sustainable Locomotion, and Photoelectric Conversion. (27th November 2022) - Chang, Longfei; Wang, Dongping; Huang, Zhishan; Wang, Chaofan; Torop, Janno; Li, Bo; Wang, Yanjie; Hu, Ying; Aabloo, Alvo
Abstract: The prospects of endowing artificial robotics or devices with increasingly complex and emergent life‐like behaviors have attracted growing interest in the soft functional materials that mimic the versatile motions of living creatures in the iridescent nature. However, despite the flourishing achievements so far, soft actuators capable of sensitive multi‐stimulus responses and self‐sustainable movements, have been extensively pursued to reduce control complexity yet remains a challenging target. Here, through material‐structural synergistic design incorporating stress‐mismatching structure, high pseudo‐negative coefficient of thermal expansion of perfluoro‐sulfonic acid ionomer, comprehensive converting properties of carbon nanotube, and anisotropic large thermal expansion of PE polymer, an ionomer‐based bilayer actuator is proposed, presenting high‐performance actuation of various forms and nice stability, responsive to light (including sunlight without focusing, LED light), low voltage, mild heating, and humidity/solvent change. With a built‐in structural feedback loop, the actuation performances are further explored to realize intelligent systems, including: 1) self‐sustainable locomotion under sunlight irradiation with adjustable photophobic and phototropic direction as well as adaption to different topographies and loading conditions, 2) self‐sustainable oscillation and solar‐electric generating, and 3) bionic floristic reaction according to environmental change. These diversified actuation modes allow promising following‐up designs for bio‐hybrid soft robotics fueled by and harmonized with natural environments. Abstract : A versatile intelligent actuator is constructed, exhibiting large deformation with various forms and high stability, responding to sunlight, electricity, and humidity/solvent change. Its reaction under natural environmental change is further demonstrated in prototypes including 1) a sustainable robot with adjustable photophobic/phototropic locomotion as well as adaptive marching ability, 2) a solar‐electric generator, and 3) bionic flowers interact with environmental changes.